Pembuatan Elektrokardiogram dan Penentuan Interval QRS secara Otomatis: Aprilia Tri Astuti, Nuryani Nuryani, Anik Lestari - Aprilia Tri Astuti Aprilia Tri Astuti; Nuryani Nuryani; Anik Lestari Anik Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
In this research, system design electrocardiogram (EKG) that is equipped with a QRS interval determination system automatically. ECG systems created using arduino and computer. The results of this research are implemented using software processing. Cardiac signal data used in this research were taken of patients. To determine the QRS interval, the first is the determination of the peak position R. Peak position R is then used to determine the position of the point Q and the position of the point S. Result for accuracy determination QRS interval in this research amounted to 95.89%.